ALS patients with concurrent neuroinflammatory disorders; a nationwide clinical records study. Issue 3 (3rd April 2022) - Longinetti, Elisa; Sveinsson, Olafur; Press, Rayomand; Ye, Weimin; Ingre, Caroline; Piehl, Fredrik; Fang, Fang
Abstract: Objective: To determine if inflammation in proximity of the motor unit may contribute to neurodegeneration in amyotrophic lateral sclerosis (ALS). Methods: We identified all patients diagnosed in Sweden with concurrent ALS and multiple sclerosis (MS), myasthenia gravis (MG), inflammatory polyneuropathies (IP), or dermatopolymyositis (DMPM) during 1991–2014 according to the Swedish Patient Register ( N = 263). We validated medical records for 92% of these patients (18 records were not retrieved and three did not contain enough information) and compared patients with a confirmed overlap ( N = 28) with an independent sample of patients with solely ALS ( N = 271). Results: Ninety-one patients were deemed as not having ALS (34.6%). Among the remaining 151 with validated ALS, 12 had also a confirmed MS diagnosis, nine a confirmed MG diagnosis, four a confirmed IP diagnosis, and three a confirmed DMPM diagnosis. Seventeen of the patients were women and 11 were men. Seventy-nine percent of the patients with a confirmed overlap had MS, MG, IP, or DMPM diagnosed prior to ALS. Compared to patients with only ALS, the concurrent patients were significantly older at symptoms onset, had higher prevalence of bulbar onset, but used Riluzole and noninvasive ventilation less frequently. Conclusions: We found that a high concurrence of ALS and MS/MG/IP/DMPM diagnoses is largely due to diagnostic uncertainty. A minority of patients had a true concurrence, where MS, MG, IP, and DMPM preceded the ALS diagnosis, which might be due to chance alone. Four patients were diagnosed with MG shortly after onset of ALS, suggesting that neurodegeneration might trigger autoimmunity.